THE IMPLEMENTATION OF BLOOM’S TAXONOMY ON THE ENGLISH SUMMATIVE TEST ITEMS FOR SECOND YEAR SENIOR HIGH SCHOOL STUDENTS IN ACADEMIC YEAR 2015/2016 - Nurul Soraya Saragih; Indra Hartoyo; Johannes Jefria Gultom (Universitas Negeri Medan, 2017)
This study aimed to analyze the distribution of cognitive level of Bloom’s Taxonomy in English Summative Test items for reading comprehension in odd and even semesters of second year students in SMAN 1 in Tebing Syahbandar academic year 2015/2016. The method of this research is descriptive qualitative research for collect, analyze and classify reading questions based on revised of Bloom’s Taxonomy. The data of this study were taken from English Summative Test for eleventh grade of SMAN 1 Tebing Syahbandar. The results of this study are: for odd semester C1 (69.23%), C2 (15.38%), C3 (7.69%), C4 (7.69%), C5 (0%) and C6 (0%); and for even semester C1 (38.89%), C2 (5.56%), C3 (0%), C4 (55.56%), C5 (0%) and C6 (0%). Adapted by Sudjana (2009), these results do not achieve proportion of thinking order skill that the total of C1 and C2 is 30%, C2 and C3 is 40%, C4 and C5 is 30%. It shows that the distribution of cognitive level of Bloom’s Taxonomy in English Summative Test items for reading comprehension in odd and even semesters of second year students in SMAN 1 in Tebing Syahbandar academic year 2015/2016 are not appropriate.Key words: English summative test, reading comprehension questions, revised Bloom’s Taxonomy.